2012
DOI: 10.1093/infdis/jis513
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 Latent Infection in Patients With Glioma

Abstract: The etiology of glioma remains unclear so far. Human herpesvirus 6 (HHV-6) might be associated with glioma, but there is no direct evidence to support this. High percentages of HHV-6 DNA and protein were detected in tissue from gliomas, compared with normal brain tissue. In addition, a strain of HHV-6A was isolated from the fluid specimens from glioma cysts. High levels of interleukin 6 (IL-6), interleukin 8 (IL-8), tumor necrosis factor α, and transforming growth factor β (TGF-β) were detected in the cyst flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 14 publications
5
43
1
4
Order By: Relevance
“…HHV-6 infection may be associated with the nodular sclerosing (NS)-type Hodgkin lymphoma and angioimmunoblastic T cell lymphoma (AITL). In addition, recent studies from our group and others demonstrated that HHV-6 may also be associated with glioma (5)(6)(7)(8).…”
mentioning
confidence: 69%
“…HHV-6 infection may be associated with the nodular sclerosing (NS)-type Hodgkin lymphoma and angioimmunoblastic T cell lymphoma (AITL). In addition, recent studies from our group and others demonstrated that HHV-6 may also be associated with glioma (5)(6)(7)(8).…”
mentioning
confidence: 69%
“…Therefore, we cannot exclude that some other nontested RNA transcripts, potentially different from those known to be associated with latency in human cells, are expressed during HHV-6A infection in the murine brain and participate in the persistence of HHV-6A. Viral RNA and proteins are very rarely detected in the brain of healthy people harboring HHV-6A DNA without HHV-6-related pathology (7,8,12,71). In humans, HHV-6 infection of tissue in vivo seems to be much less efficient than that in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Marmosets inoculated with HHV-6A intravenously exhibited neurological symptoms, whereas those inoculated with HHV-6B were asymptomatic [75]. A strain of HHV-6A has also recently been isolated from the fluid specimens from a glioma cyst [30]. Moreover, HHV-6A was identified in 72 % of pediatric glial tumors [38].…”
Section: Distinct Epidemiology and Disease Associationsmentioning
confidence: 99%